2011
DOI: 10.1111/j.1365-263x.2011.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I can’t relate it to teeth’: a qualitative approach to evaluate oral health education materials for preschool children in New South Wales, Australia

Abstract: Producers of health education leaflets should keep the messages simple and straightforward, avoid the use of medical jargon, and use pictorial aids to improve communication with parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…This was found to be consistent with the findings of the present study where parent/caregiver oral behaviours such as dental attendance and dietary habits were associated with a higher rate of visible caries experience in the Poisson regression model. To be effective, oral health promotion should therefore include an understanding of parent and caregiver knowledge and attitudes [33] and oral health advice must be clear and appropriate [34]. …”
Section: Discussionmentioning
confidence: 99%
“…This was found to be consistent with the findings of the present study where parent/caregiver oral behaviours such as dental attendance and dietary habits were associated with a higher rate of visible caries experience in the Poisson regression model. To be effective, oral health promotion should therefore include an understanding of parent and caregiver knowledge and attitudes [33] and oral health advice must be clear and appropriate [34]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that improvement in dental health education materials is one of the concrete methods of increasing oral health knowledge. When this is combined with other health promotion interventions, will reduce oral health disparities [8].…”
Section: Discussionmentioning
confidence: 99%
“…The study is nested within a birth cohort study that recruited 1,033 mothers with newborn children in South West Sydney in 2010 (20,21). The purpose of the main study is to investigate the relationship between early childhood feeding practices and dental caries in preschool children.…”
Section: Methodsmentioning
confidence: 99%